Inventory of selected raptor, colonial, and sensitive bird species in the Athabasca oil sands area of Alberta - Ealey, D.; Beaver, R.; Munson, B.; Fyfe, R. (1980)
A three-year inventory of selected rare, endangered and sensitive bird species in the Athabasca Oil Sands area of northeastern Alberta was completed in the late summer of 1977. Aerial and ground surveys of the Alberta Oil Sands Environmental Research Program (AOSERP) study area and selected adjacent areas were conducted. Three major habitat types were investigated: the boreal mixed-wood forest of the Birch Mountains area; the jack pine sandplains south of Lake Athabasca and the Canadian Shield north of Lake Athabasca. Three major groups of birds were surveyed: raptors, colonial birds, and specified sensitive species. Locations of nest sites and colonies were noted and described. No attempt was made to determine the absolute abundance of each species in the AOSERP study area, as the aerial surveillance techniques employed do not justify such an estimation. The exception to this were two species whose total population in the AOSERP study area was restricted to very small areas and therefore could be readily determined: White Pelicans and Peregrine Falcons. Each of these species was investigated in considerable detail and, the data reported in separate publications. Recommendations were made for: 1. Further, more intensive surveys of part of the AOSERP study area in order to determine phenology and numbers of initial breeders more accurately; and 2. Additional surveys of the Canadian Shield area which was incompletely surveyed during this study. Observations of foraging behaviour of a breeding pair of Bald Eagles were conducted in the Birch Mountains, 90 km northwest of Fort McMurray, Alberta, from mid-summer to early fall, 1977. Bald Eagles foraged almost exclusively on fish, although gull wings and a merganser skull were found below nest trees. Nest trees were generally located less than 50 m from water. Active nests were more frequently located on islands and peninsulas. The nest trees were usually tall and broad and included jack pine, spruce, and less frequently trembling aspen. Live trees were preferred over ...